Determinants of repayment behaviour of MFI clients in the context of COVID-19: a case study of Lalitpur District, Nepal - Shrestha, Sabeena; Thapa, Bharat Singh (Nepalese Journal of Insurance and Social Security, 2021)
This paper investigated factors affecting repayment performance of MFI clients in the context of COVID-19. Business characteristics, borrowers’ characteristics and lenders’ behavior were identified and predictors of loan repayment. A telephone interview using a full-fledged questionnaire was conducted among randomly chosen 160 loan clients of various microfinance institutions in Mahalaxmi municipality of Lalitpur district during Covid 19 pandemic (June-July, 2020). The descriptive statistics, correlation analysis, binary logistic regression analysis analyzed the data and qualitative analysis is done to support the result of research. The finding of study reveals that age of the borrower, educational level of borrowers, types of the business and profit generated business influence the repayment of loan. However, family size, skills, age of business, work performance, transparent communication and clarity of MFI policy does not have any impact on repayment of loan. COVID-19 pandemic has affected all types of business and created poor cash flow in the market and due to lockdown, the source of income has been decreased which causes large number of delay repayment of monthly installment is decrease in profit due to decrease in revenue of the business.